'At this point, the lichens in the trees are their only means of survival': A History of Tree Cutting for Winter Reindeer Fodder by Sami People in Northern Sweden. (1st May 2011) - Berg, Anna; Gunnarsson, Bjorn; Ostlund, Lars
Abstract : The importance of land use history and its impact on ecological systems has recently been recognised, primarily because most 'natural areas' have been found to have experienced greater human interference than previously assumed. The extent of forest exploitation in pre-industrial times, especially by native people, has been consistently underestimated. In northern Sweden all the reindeer are herded by the native Sami people. During the winter, reindeer usually feed on ground lichens, which they dig for under the snow. Traditionally, trees with arboreal lichens were cut to provide supplementary food when adverse snow conditions prevented grazing. The stumps from such cuttings are commonly known as 'lichen-stumps' and they can be found in the few remaining unmanaged forest areas. In this study we examine the history, ecology and extent of this specific aspect of forest use by using an integrated approach involving both historical records and field studies. We found that the cutting of trees for lichens was a widespread practice during harsh winters, that significant numbers of trees were cut and that it ceased at the end of the nineteenth century, coinciding with large-scale changes in the land use of northern Scandinavia.